Pengaruh Kualitas Audit, Likuiditas, dan Solvabilitas terhadap Opini Audit Going Concern : Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Batu Bara Tahun 2014 – 2017 - Rohmat Rohmat; Suharmadi Suharmadi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The auditor's responsibilities include not only assessing the accuracy of financial statements and detecting fraud, but also evaluating the company's ability to continue its business on an ongoing basis. This responsibility arises from the expectations of shareholders and other stakeholders that auditors provide timely and relevant information about the company's future prospects to support rational and evidence-based investment decision-making. In this context, audit opinions related to business continuity are an important instrument in reducing information asymmetry between management and investors. This study aims to analyze the impact of liquidity, solvency, and audit quality on the issuance of business continuity declarations. The research sample consisted of coal mining companies listed on the Indonesia Stock Exchange between 2014 and 2017, a period marked by fluctuations in commodity prices and global economic uncertainty. Logistic regression is used as an analysis method because dependent variables are dichotomous. The results showed that audit quality had a significant negative impact on the issuance of business continuity declarations, while liquidity and solvency did not have a significant impact on the issuance of the declarations, indicating that the factors of governance and auditor independence were more decisive than short-term financial conditions.